The effect of malaysian stingless bee, trigona spp. Honey in promoting proliferation of the undifferentiated stem cell - Mohamad, Mohd Amin Marwan; Mazlan, Muhammad Alif; Ibrahim, Muhammad; Mat Yusof, Afzan; Shamsuddin, Shamsul Azlin Ahmad; Nik Hassan, Nik Fakhuruddin; Muhammad, Hussin; Md Isa, Muhammad Lokman (Malaysian Society for Molecular Biology and Biotechnology, 2019)
Stem cells provide various potential applications in regenerative medicine through its ability of self-renewal and differentiation. Among the various stem cells, dental pulp stem cells (DPSCs) have shown encouraging results in their ability to regenerate. Honey has been used in traditional culture as a natural medicine in supporting wound healing. Yet, very few studies on honey were conducted for its potential as a proliferative agent for stem cells. The aim of this study is to evaluate the stability of two Trigona spp. honeys (1 and 2) added in culture media and its proliferative effect on DPSCs. Both honeys were diluted with standard culture medium through dilution process to prepare the concentrations of 0.01%, 0.04%, 0.10% and 0.25%. DPSCs were treated with the diluted honeys for 24 hours. The proliferative activity was determined through the images taken using an inverted microscope for every six hours. In addition, the MTT assay was conducted to determine the cell viability of DPSCs when treated with both honey 1 and 2 at various concentrations. The results showed a stable culture media added with honey for three days and a dose-dependent proliferative effect of both Trigona spp. honey samples on DPSCs. Optimum proliferative effects were observed at 24 hours for both Trigona spp. honey 1 and 2 on DPSCs. The optimum concentration of Trigona spp. honey 1 was from 0.04% to 0.10% and Trigona spp. honey 2 was below 0.01%. It is concluded that Trigona spp. honey has a promising proliferative effect on DPSCs. © 2019, University of Malaya. All rights reserved.